Classification models based on the level of metals in hair and nails of laryngeal cancer patients: diagnosis support or rather speculation?. Issue 3 (11th March 2015) - Golasik, Magdalena; Jawień, Wojciech; Przybyłowicz, Agnieszka; Szyfter, Witold; Herman, Małgorzata; Golusiński, Wojciech; Florek, Ewa; Piekoszewski, Wojciech
<x xml:space="preserve">Abstract</x> Several larynx cancer prediction models were built and each was weighted according to their performance.